THE ROLE OF AgNPs AND AB Mix IN THE GROWTH OF Aglaonema 'LADY VALENTINE' IN VITRO & EX VITRO - Damasa Ines Larrisa; Pangesti Nugrahani; Sri Wiyatiningsih (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Aglaonema ‘Lady Valentine’ is a popular ornamental plant with significant economic value. Conventional propagation methods have limitations, making tissue culture and acclimatization viable alternatives. However, low shoot multiplication and slow acclimatization remain major challenges. This study investigated the effects of silver nanoparticles (AgNPs) and AB Mix nutrient concentrations on in vitro and ex vitro plantlet growth using a two-factorial completely randomized design with four levels and three replications. The results showed varied growth responses, with the best performance observed in the 2 ppm AgNPs and 3 ml/L AB Mix treatment, which increased plantlet height, volume, and visual health. In ex vitro conditions, both 2 ppm and 3 ppm AgNPs combined with 3 ml/L AB Mix supported better plantlet adaptation, as seen in increased height, number of leaves and shoots, and seedling viability. Overall, the combination of 2 ppm AgNPs and 3 ml/L AB Mix proved most effective for enhancing multiplication and acclimatization